Теоретико-методичні засади навчання теоретичної фізики майбутніх учителів фізики - Школа, Олександр Васильович (Видавець Ткачук О. В., 2015)
У монографії запропоновано концепцію навчання курсу теоретичної фізики як чинника фундаменталізації професійної підготовки майбутніх учителів фізики в контексті сучасної парадигми вищої освіти. Обґрунтовано теоретико-методичні засади створення авторської моделі відкритої та гнучкої методичної системи навчання дисципліни на основі органічного поєднання принципів фундаментальності та професійної спрямованості, реалізації діяльнісного, особистісно зорієнтованого та компетентнісного підходів, раціонального поєднання традиційних та інноваційних технологій навчання, спрямованих на самореалізацію, професійне зростання й самоствердження особистості майбутнього вчителя фізики. Для науково-педагогічних працівників, викладачів, учителів, аспірантів, магістрантів, студентів фізичних спеціальностей вищих навчальних закладів
Theoretical and methodological basis of theoretical physics teaching of future teachers of physics
The thesis for the first time offers the theoretical and methodological principles of teaching Theoretical Physics of future teachers of physics based on individually oriented, activity and competency approaches. This combination will achieve the unity of basic and professional training of future specialists. The content of the modern concept of teaching Theoretical Physics at pedagogical universities includes the following statements: • the course of studies is an integral methodical system that includes goals, objectives, content and technologies, united by a common methodology of construction and implementation in conformity with the principle of integration of fundamental orientation and professional training of future Physics teachers; • the methodical system of Theoretical Physics’ teaching is an invariant part of fundamental training of future Physics teachers. It involves the forming of the professional competence, which affects it’s all other components (social and personal, general scientific, specialized and professional etc.); • the necessary conditions of forming of the professional competence of students are: a) fundamentality of general scientific training; b) providing creative activity and self-realization of students on the basis of the developing training methodology, competence and individually oriented approaches, the optimal combination of traditional and innovative learning technologies; c) implementation of the continuity principle and relationship of the courses of General and Theoretical Physics in the system of training of Physics teachers; d) introduction of module-rating system of the educational process, systematic and continuous monitoring of the quality of students’ educational achievements; • the structure of the course of studies should be a systematic unity of content-related and procedural components. The first one contains the main subject (invariant) and auxiliary (variable) knowledge. The invariant part includes the material that combines the empirical basis and core of fundamental physical theories, the variant one - the consequences of theories, application and professionally oriented knowledge. The process component contains methods, means and kinds of teaching students, as well as organizational forms of teaching, which are in congruence with goals, content and nature of their future professional activities; • the basis of Theoretical Physics teaching should be the formation of the person of a future Physics teacher, the formation of a cultured and educated person with a broad scientific outlook and appropriate style of thinking, who lives and works in the world of modern technology. This means that the educational process should be based on the transferring from information and illustrative charts, which are oriented to transferring from passive getting of knowledge to search and creative educational process, learner-oriented, aimed also at the training of professionally significant personal qualities, the development of cognitive activity, intellectual and creative abilities and the formation of students’ attitudes toward the knowledge and the process of getting them as a great value. The author for the first time under the conditions of a credit-transfer educational organization of teaching at pedagogical university suggested the methodical system of training the course of studies focusing on the formation of an integrated system of fundamental knowledge and professional competence of future Physics teachers. This methodical system is based on the relationship of scientifically based components (target, content procedure, diagnostic and outcome components) and provides keeping to conceptual approaches and organizational and pedagogical conditions that ensure effective implementation of it. The target component is a basic, backbone element of the methodological system. It defines the functions of all other components and provides the students' awareness of the general purpose and the main tasks of learning the discipline at pedagogical university, which depend on the requirements of the society and the state standard of higher education. The basis of the methodical system is a content-related and procedural component which contains proper train training material and effective didactic appliances according to the core curriculum and composed by O.Shkola module program. The methodical system also includes the means of systematic and continuous diagnostics of students’ progress, criteria and showings of the levels of their fundamental knowledge of Theoretical Physics. The author also for the first time has developed a module program of the course of studies “Theoretical Physics” for pedagogical universities. Having based on the structuring knowledge elements, O.Shkola identified and elaborated the content of scientific and theoretical, practical and activity components of professional competence of students for each thematic module in the form of "students know / understand" (the meaning of physical concepts and values, phenomenon, effects, methods, experiments, laws and consistent patterns, principles, postulates, theorems, equations, and physical constants); "Students can" ( explain, represent and analyze, simulate, detect and remove, solve, draw philosophy-natured conclusions).Generalizations presented in this manner allow to distinguish the basic material as fundamental, which has the most important professional and pedagogical value and the support material, and then present them as a system which ensures the validity of knowledge on the long term, develops abilities and helps to master new information quickly. The author developed and implemented the educational and methodical complex of the course of studies of “Theoretical Physics” (illustrated by an example of the course “Thermodynamics and Statistical Physics”) of future Physics teachers. The author experimentally demonstrated pedagogical appropriateness and effectiveness of the methodical system of forming and developing scientific outlook of future specialists
Keywords: фундаменталізація освіти; теоретична фізика; фундаментальна підготовка вчителів фізики; фахова компетентність вчителя фізики; методична система навчання теоретичної фізики; навчально-методичний комплекс; науковий світогляд; fundamentalization of education; theoretical physics; fundamental training of physics teachers; professional competence of physics teacher; methodical system of theoretical physics training; educational and methodical complex; scientific worldview